Cover Feature: High‐Performance Ytterbium‐Doped V2O5 ⋅ H2O Binder‐Free Thin‐Film Electrodes for Supercapacitors (11/2021). Issue 11 (10th May 2021) - Yang, Shu; Cen, Yuan; Hu, Bingbing; Xu, Chuanlan; Li, Yan; Yu, Jingjing; Hu, Bihao; Meng, Jiazhi; Yu, Danmei; Chen, Changguo
Abstract : The Cover Feature shows a honeycomb‐like Yb‐doped V2 O5 ⋅ n H2 O binder‐free thin‐film electrode synthesized by a simple and convenient sol–gel method. This electrode exhibits superior electrochemical performance and high specific capacity. The assembled Yb‐V2 O5 ⋅ n H2 O//V2 O5 ⋅ n H2 O@OSP supercapacitor device delivers excellent cycling stability. More information can be found in the Article by S. Yang et al .